Mechanism of valve failure and efficacy of reintervention through catheterization in patients with bioprosthetic valves in the pulmonary position - Ryan Callahan; Lisa Bergersen; Christopher W Baird; Diego Porras; Jesse J Esch; James E Lock; Audrey C Marshall (Annals of Pediatric Cardiology, 2017)
Background: Surgical and transcatheter bioprosthetic valves (BPVs) in the pulmonary position in patients with congenital heart disease may ultimately fail and undergo transcatheter reintervention. Angiographic assessment of the mechanism of BPV failure has not been previously described. Aims: The aim of this study was to determine the mode of BPV failure (stenosis/regurgitation) requiring transcatheter reintervention and to describe the angiographic characteristics of the failed BPVs and report the types and efficacy of reinterventions. Materials and Methods: This is a retrospective single-center review of consecutive patients who previously underwent pulmonary BPV placement. (surgical or transcatheter) and subsequently underwent percutaneous reintervention from 2005 to 2014. Results: Fifty-five patients with surgical. (41) and transcutaneous pulmonary valve. (TPV) (14) implantation of BPVs underwent 66 catheter reinterventions. The surgically implanted valves underwent fifty reinterventions for indications including 16 for stenosis, seven for regurgitation, and 27 for both, predominantly associated with leaflet immobility, calcification, and thickening. Among TPVs, pulmonary stenosis. (PS) was the exclusive failure mode, mainly due to loss of stent integrity. (10) and endocarditis. (4). Following reintervention, there was a reduction of right ventricular outflow tract gradient from 43 ± 16 mmHg to 16 ± 10. mmHg (P < 0.001) and RVp/AO ratio from 0.8 ± 0.2 to 0.5 ± 0.2 (P < 0.001). Reintervention with TPV placement was performed in 45. (82%) patients. (34 surgical, 11 transcatheter) with no significant postintervention regurgitation or paravalvular leak. Conclusion: Failing surgically implanted BPVs demonstrate leaflet calcification, thickness, and immobility leading to PS and/or regurgitation while the mechanism of TPV failure in the short- to mid-term is stenosis, mainly from loss of stent integrity. This can be effectively treated with a catheter.based approach, predominantly with the valve-in-valve technique.